A comparison of temporal pathways to self-harm in young people compared to adults: A pilot test of the Card Sort Task for Self-harm online using Indicator Wave Analysis - Lockwood, Joanna; Babbage, Camilla; Bird, Katherine; Thynne, Imogen; Barsky, Andrey; Clarke, David D.; Townsend, Ellen (Frontiers in Psychiatry, 2023)
Background: Self-harm is complex, multifaceted and dynamic, typically starts in adolescence and is prevalent in young people. A novel research tool (the Card-sort Task for Self-harm; CaTS) offers a systematic approach to understanding this complexity by charting the dynamic interplay between multidimensional factors in the build-up to self-harm. Sequential analysis of CaTS has revealed differences in key factors between first and most recent episode of self-harm in adolescence. Rates of self-harm typically decline post adolescence, but self-harm can continue into adulthood. Comparison between factors linked to self-harm in young people versus adults will inform understanding of how risk unfolds over time and clarify age-specific points for intervention. A pilot online adaptation (CaTS-online) and new method (Indicator Wave Analysis; IWA) were used to assess key factors in the build-up to self-harm. Methods: Community-based young people (n= 66; 18-25 years, M=21.4; SD=1.8) and adults (n=43; 26-57 years, M=35; SD=8.8) completed CaTS-online, documenting thoughts, feelings, events and behaviours over a 6 month timeline for first ever and most recent self-harm. Notable interdependence between factors and timepoints was identified using IWA. Results: Positive emotion at and immediately after self-harm exceeded threshold for both groups for both episodes. Feeling better following self-harm was more pronounced for first ever episodes. Impulsivity was an important immediate antecedent to self-harm for both groups at both episodes but most markedly for young people. Acquired capability was notable for adults’ most recent episode, suggesting this develops over time. Burdensomeness was only more notable for adults and occurred at 1-week prior to a recent episode. Both groups revealed patterns of accessing support that was helpful and unhelpful. Conclusions: Commonalities and differences in the temporal organisation of factors leading to and following self-harm were identified in young people and adult pathways which shed light on age-specific factors and possible points of intervention. This has implications for clinical supports and services around approaches to positive feelings after self-harm (especially for first ever self-harm), feeling of burdensomeness, impulsivity and acquired capability leading up to self-harm. Support is provided for card-sort approaches which enable investigation of the complex and dynamic nature of pathways to self-harm.